Overview of the Genetic Diversity of African Macrotermes (Termitidae: Macrotermitinae) and Implications for Taxonomy, Ecology and Food Science - Bronwyn Egan; Zwannda Nethavhani; Barbara van Asch (Insects, 2021)
Macrotermes termites play important ecological roles and are consumed by many communities as a delicacy and dietary complement throughout Africa. However, lack of reliable morphological characters has hampered studies of Macrotermes diversity in a wide range of scientific fields including ecology, phylogenetics and food science. In order to place our preliminary assessment of the diversity of Macrotermes in South Africa in context, we analysed a comprehensive dataset of COI sequences for African species including new and publicly available data. Phylogenetic reconstruction and estimates of genetic divergence showed a high level of incongruity between species names and genetic groups, as well as several instances of cryptic diversity. We identified three main clades and 17 genetic groups in the dataset. We propose that this structure be used as a background for future surveys of Macrotermes diversity in Africa, thus mitigating the negative impact of the present taxonomic uncertainties in the genus. The new specimens collected in Limpopo fell into four distinct genetic groups, suggesting that the region harbours remarkable Macrotermes diversity relative to other African regions surveyed in previous studies. This work shows that African Macrotermes have been understudied across the continent, and that the genus contains cryptic diversity undetectable by classic taxonomy. Furthermore, these results may inform future taxonomic revisions in Macrotermes, thus contributing to advances in termitology.